SENSORIAL EVALUATION OF THE COMPOTE AND SWEET IN SYRUP ELABORATED WITH GREEN FIG - Caetano, Priscilla Karim [UNESP]; Mendonca, Veridiana Zocoler de [UNESP]; Daiuto, Erica Regina [UNESP]; Vieites, Rogerio Lopes [UNESP] (Univ Federal Mato Grosso, 2015)
The aim of this work was to verify the sensorial preference of the fig compote and sweet in syrup in function of preparation method. Three treatments were accomplished: fig compote - thermal treatment for 20 minutes and without cooking in the syrup (T1), sweet of fig - thermal treatment for 10 minutes and cooking in the syrup for 10 minutes (T2) and sweet of fig: without thermal treatment and cooking in the syrup for 20 minutes (T3). The sweets were homogenized, fruit and syrup, and evaluated for the soluble solids content ((o)Brix), hidrogenionic potential (pH) and titratable acidity (citric acid g.100g pulp(-1). Samples of the three treatments were submitted to the sensorial evaluation by 50 consumers group of fruits that appreciate fig, compotes and sweet of fruits, without restrictions as for the age, to the sex and the consumption frequency. The values of all of the appraised physiochemical attributes in this research are in agreement with the literature and legislation for this product type. For sensorial analysis, the treatment two obtained superior notes to the other treatments, demonstrating that the fig cooking in syrup for 10 minutes showed higher acceptability of assessors. Difference was not verified in relation to the sex in the preference for the product.
Keywords: Ficus carica L.; processing; aceptability